2005
DOI: 10.1182/blood-2004-07-2676
|View full text |Cite
|
Sign up to set email alerts
|

Single infusion of myeloid progenitors reduces death from Aspergillus fumigatus following chemotherapy-induced neutropenia

Abstract: Hematopoietic progenitors committed to the myeloid lineage, the common myeloid and granulocyte-monocyte progenitors (CMP/GMP), have been shown to protect against opportunistic pathogens following myeloablative radiation; however, the efficacy of this approach has not been studied in the setting of chemotherapyinduced neutropenia. In this mouse model, the infusion of CMP/GMP on the day after 5-fluorouracil (5-FU) administration (D؉1) resulted in a significant increase in the number of splenic neutrophils by D؉8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…mice at 2 weeks after HSCT. Our motivation to examine this stemmed from studies by Brown and colleagues, 15,16 in which these investigators clearly demonstrated that the inclusion of MPCs (both CMPs and GMPs) with HSCs during HSCT promoted the rapid appearance of myeloid cells necessary to protect these mice from microbial or fungal infection, while the transplant of HSCs alone required a considerably longer time to repopulate the myeloid populations necessary for the same degree of protection from infection. However, these previous studies did not address whether the included MPCs directly contributed to the increased myeloid cell populations observed after HSCT.…”
Section: Ccr7 ؊/؊ Mice Show Increased Numbers Of Hscs and Gmps In Bm mentioning
confidence: 99%
See 2 more Smart Citations
“…mice at 2 weeks after HSCT. Our motivation to examine this stemmed from studies by Brown and colleagues, 15,16 in which these investigators clearly demonstrated that the inclusion of MPCs (both CMPs and GMPs) with HSCs during HSCT promoted the rapid appearance of myeloid cells necessary to protect these mice from microbial or fungal infection, while the transplant of HSCs alone required a considerably longer time to repopulate the myeloid populations necessary for the same degree of protection from infection. However, these previous studies did not address whether the included MPCs directly contributed to the increased myeloid cell populations observed after HSCT.…”
Section: Ccr7 ؊/؊ Mice Show Increased Numbers Of Hscs and Gmps In Bm mentioning
confidence: 99%
“…17 It was recently demonstrated that an infusion of myeloid progenitor cells (MPCs; CMPs and GMPs) during HSCT provided protection from IA in a murine model, compared with HSCs alone. [15][16] Protection was mediated by enhanced immune reconstitution, which included a significant increase in the number of neutrophils present after HSCT. Thus, accelerated myeloid reconstitution through the use of MPCs during HSCT may be an attractive therapeutic option.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloid progenitor cells have been shown to be of special interest in this respect because they can be cryopreserved, used independent of major histocompatibility complex matching, and provide rapid and mostly transient engraftment that provides protection against bacterial and fungal pathogens (86,87,92).…”
Section: Reviewmentioning
confidence: 99%
“…However, progenitor cells are capable of partially restoring functional hematopoiesis for a limited period of time [26][27][28] . A combination of CMP/ GMP isolated from the bone marrow has been shown to protect myeloablated mice from otherwise lethal doses of pathogenic fungus or bacteria in syngeneic and allogeneic mouse models 26,29,30 . Furthermore, purified populations of CMP or MEP but not GMP protect lethally irradiated congenic mice from death in a dose-dependent manner 28 .…”
Section: Use Of Progenitors In Radiation Casualtiesmentioning
confidence: 99%